Health care quality model of family physician program in Iran (mixed method) - Alireza Heidarian naeini; Ghahraman Mahmoudi; Jamshid Yazdani Charati (Babol University of Medical Sciences, 2022)
Background: There has been a growing international evolution of the role and purpose of quality improvement in primary health care. The present study aimed to develop a quality model of the Family Physician program in Iran. Methods: In the qualitative part of these mixed-method studies, grounded theory was used according to the systematic method of Strauss and Corbin. Semi-structured interviews were conducted with recipients and providers of Family Physician cares in the pilot provinces of Iran in 2020 to 2021 and continued until the theoretical saturation based on the purposive technique. The qualitative evaluation of the model was performed and approved. Structural equation modeling and Amos software were used to quantify the model. Results: The results of the structural equation analysis showed that the conceptual model of the research with chi-square test was 2.96 and RMSEA= 0.066, GFI=0.860 are well fitted. Structure, context, process, accountability, attitude, and empowerment factors directly and indirectly provide good predictors for the quality of care in the family physician program. The most important research findings in the field of quality improvement in the family physician's cares included factors such as developing the attitude and vision of society, providers and policymakers in health subject and health needs, simultaneously corrections in all levels of the referral system, attention and adaptation to the context of society, developing the infrastructures and improving the related processes, systematic appraisal, and accountability and pay attention to the empowerment. Conclusion: To achieve the quality of care in the family physician program, we need change and development in our attitudes, context, infrastructures and processes, accountability and empowerment systems, and overall modification.